복강경수술 훈련용 담낭 절제술 시뮬레이션 개발 - 김영준; Fr？d？rick Roy; 이승빈; 서준호; 이득희; 박세형 (한국CDE학회, 2012)
Laparoscopic surgery is a surgical procedure which uses long laparoscopic instruments through tiny holes in abdomen while watching images from a laparoscopic camera through umbilicus. Laparoscopic surgeries have many advantages rather than open surgeries, however it is hard to learn the surgical skills for laparoscopic surgery. Recently, some virtual simulation systems for laparoscopic surgery are developed to train novice surgeons or resident surgeons. In this study,we introduce the techniques that we developed for laparoscopic surgical training simulator for cholecystectomy (gallbladder removal), which is one of the most frequently performed by laparoscopic surgery. The techniques for cholecystectomy simulation include modeling of human organs (liver, gallbladder, bile ducts, etc.), real-time deformable body calculation, realistic 3D visualization of surgical scene, high-fidelity haptic rendering and haptic device technology, and so on. We propose each simulation technique for the laparoscopic cholecystectomy procedures such as indentifying cystic duct and cystic artery to clamp and cut, dissecting connective tissues between the gallbladder and liver. In this paper, we describe the techniques and discuss about the results of the proposed cholecystectomy simulation for laparoscopic surgical training.